2009
DOI: 10.1007/s10067-009-1147-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fibromyalgia: the role of violence against women

Abstract: The objectives of the study were to analyse the association between fibromyalgia (FM) and violence against women and to explore the association between FM and sociodemographic factors, social support and psychological distress. A case-control study was conducted in a Spanish hospital. Cases were women diagnosed with FM, with no signs of any other type of inflammatory rheumatic disorder, who were seen at the Rheumatology Department of the hospital. Controls were women not diagnosed with FM who were seen at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…Some have theorized that stress itself results from the interaction between individuals and their environments, and a distress reaction results from either an abnormal and maladaptive response to stressful and potentially traumatic circumstances or when a person perceives (appraises) personal resources to be insufficient to tolerate the stressor (32). For instance, childhood victimization (63), high frequency of abuse (64), and history of sexual abuse-rape (62,65) have been reported in women with poor physical and somatic conditions (11,14,66).…”
Section: Discussionmentioning
confidence: 98%
“…Some have theorized that stress itself results from the interaction between individuals and their environments, and a distress reaction results from either an abnormal and maladaptive response to stressful and potentially traumatic circumstances or when a person perceives (appraises) personal resources to be insufficient to tolerate the stressor (32). For instance, childhood victimization (63), high frequency of abuse (64), and history of sexual abuse-rape (62,65) have been reported in women with poor physical and somatic conditions (11,14,66).…”
Section: Discussionmentioning
confidence: 98%
“…Among these, six were case-control studies. Three studies reported a higher incidence of childhood sexual (range 7-37% v. 6-22%) and physical abuse (range 8-34% v. 4-12%) in FM patients than in controls (Boisset-Pioro et al 1995;Ruiz-Perez et al 2009;Smith et al 2010). Anderberg et al (2000) also demonstrated that FM patients had a higher prevalence of childhood sexual (7.5% v. 5%) and physical or psychological abuse (27.5% v. 13%) than patients without a history of abuse.…”
Section: Childhood Sexual and Physical Abusementioning
confidence: 97%
“…La mayoría de estos estudios han hallado que una historia de vida traumática es una variable importante de análisis en el estudio de la FM, como por ejemplo ser víctima de violencia de género (Ubago Linares et al, 2005;Ruiz Pérez et al, 2008;Cantera Espinosa, 2004;Blanco et al, 2004). Mientras que aún son pocos los trabajos que estudian directamente los roles de género, el conflicto de roles, el estrés y la identidad social de género como antecedentes relacionados con la FM (Aparicio, 2002;González de Chávez, 2002;Tosal Herrero, 2007;Valls Llobet, 2002, 2006y 2007.…”
Section: Estudio Piloto: Una Aproximación Cualitativa a La Fibromialgunclassified